2001
DOI: 10.3201/eid0703.017332
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Metronidazole-ResistantBacteroides fragilis, India

Abstract: To the Editor: Members of the Bacteroides fragilis group are the most commonly isolated anaerobic pathogens in humans. Metronidazole has been the drug of choice for preventing and treating such infections for 40 years. Although B. fragilis exhibits the broadest spectrum of recognized resistance to antimicrobial agents among anaerobes, the worldwide rate of metronidazole resistance remains low, <5% (1,2). We report here the first metronidazole-resistant strain of B. fragilis from India.A 34-year-old man with my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…The results of current research showed isolated B. fragilis are sensitive to metronidazole and imipenem, which is in accordance with the findings of some researchers (12,13). However, totally resistant strains obtained from animals and human against imipenem (15,16), and strains resistant to metronidazole were also found in different studies (17,18).…”
Section: Discussionsupporting
confidence: 89%
“…The results of current research showed isolated B. fragilis are sensitive to metronidazole and imipenem, which is in accordance with the findings of some researchers (12,13). However, totally resistant strains obtained from animals and human against imipenem (15,16), and strains resistant to metronidazole were also found in different studies (17,18).…”
Section: Discussionsupporting
confidence: 89%
“…Resistance genes nimA to -F, which have been implicated in sporadic cases of metronidazole resistance in several hospitals worldwide, have been identified on transferable plasmids (56,148,279). Transferable plasmid-linked chloramphenicol acetyltransferase conferring high-level resistance was observed in a clinical isolate of Bacteroides uniformis (152).…”
Section: Mobile Genetic Elements In Bacteroidesmentioning
confidence: 99%
“…Resistance is generally attributed to changes in the nim genes or associated genes (e.g., IS) (30,56,75,259). The nim gene can be "silent" unless activated by IS elements (111).…”
Section: Continued On Facing Pagementioning
confidence: 99%
“…15,[23][24][25][26] Bacteroides spp resistance to fluoroquinolones has also increased from 1.5-12% during the past few years. 27,28 Metronidazole-resistant strains of B. fragilis have been reported in many countries, including Brazil, 29 India, 30 United States, 31 Hungary 32 and Poland, 33 and some Indian strains show very high levels of resistance (MIC 512 mg/L). 34 Therefore, anaerobic infections have reemerged as a serious health threat, and Bacteroides spp are now recognized as important pathogens.…”
Section: Introductionmentioning
confidence: 99%